Biofortification of wheat: Genetic and agronomic approaches and strategies to combat Iron and Zinc deficiency - Sharma, Dipa; Ghimire, Prakriti; Bhattarai, Shweta; Adhikari, Upama; Khanal, Saugat; Poudel, Padam Bahadur (International Journal of Environment, Agriculture and Biotechnology, 2020)
This study delves into the comprehensive overview of different agronomic and genetic approaches of wheat biofortification to combat iron and zinc deficiency. Secondary source of data is used during the study of the subject. Micronutrient deficiencies, particularly those arising from zinc (Zn) and iron (Fe), pose serious human health problems for billions of people worldwide and millions of children, who predominantly depend upon cereals-based diet, suffer from malnutrition.Wheat, being a chief staple food crop for most of the under-developed countries, should be given emphasized to make it enriched with nutrients and minerals as in many cases, it constitutes a low level of nutritional elements. Most of the nutrients are lost during milling. Biofortification acts as the most promising and economic strategic option to effectively increase the micronutrients in the edible portion of the crop. Agronomic and Genetic biofortification are the two approaches; however, genetic engineering is getting more concern for researches. This uses the techniques to enhance the bioavailability of nutrients and reduce the anti-nutrient compounds. Although there are many technologies to increase nutrient contents, biofortification is assumed to be the most sustainable. Different strategies for wheat biofortification are assessed in this paper for overcoming challenges seen during the process. We discuss promising ways to enhance iron and zinc content in wheat, highlight global wheat production scenario and malnutrition status, and also key challenges are accentuated.